Bioremediation of hexavalent chromium by endophytic fungi; safe and improved production of Lactuca sativa L. (November 2018) - bibi, Shabeena; Hussain, Anwar; Hamayun, Muhammad; Rahman, Hazir; Iqbal, Amjad; Shah, Mohib; Irshad, Muhammad; Qasim, Muhammad; Islam, Badshah
Abstract: One of the main problems of the industrialized world is the accumulation of chromium (Cr) in soil, which is a serious threat to the crops. Complete removal of Cr from the contaminated soils poses a great challenge. However, this issue can be minimised by using plant growth promoting microbes as a bioremediation tool. In the present study, healthy plants established near the University campus in Mardan were selected for the isolation of Cr resistant endophytes. From the designated plants, 114 species of endophytic fungi were isolated. Among the 114 isolated strains, 4 strains have induced resistance in L. sativa against Cr. The strains were identified as Aspergillus fumigatus, Rhizopus sp., Penicillium radicum and Fusarium proliferatum based on ITS region (18 S rDNA) homology. The isolates have removed Cr from soil and culture media as well as bio-transformed it from highly toxic hexavalent to least toxic trivalent form, thus helped the Cr stressed L. sativa to restore its normal growth. The Rhizopus Sp. CUC23 has mainly accrued Cr and detoxified intracellularly, whereas A. fumigatus ML43 and P. radicum PL17 has detoxified up to 95% of Cr extracellularly. From the results, it is concluded that the selected endophytic strains might be used as biofertilizer for healthy and safe crop production in Cr contaminated soils. Graphical abstract: Image 1 Highlights: Detoxification of hexavalent chromium by endophytic fungi in plant and soil has been reported. Four selected fungal endophytes alleviated Cr toxicity in Lactuca sativa L. The strains were able to carry out intra and extra mycelial reduction of Cr-VI to Cr-III Translocation of Cr to the edible parts was significantly reduced in endophytes associated seedlings.